PEMANFAATAN LIMBAH CAIR TEMPE DAN LIMBAH CAIR TAHU DENGAN MENGGUNAKAN INOKULUM YANG BERBEDA UNTUK PRODUKSI BIOGAS - Niluh Budi Artini; Muhammad Alwi; Umrah Umrah (Biology Department, Mathematics and natural science, Tadulako University, 2014)
This research was about “ The Usage of Liquid Waste of Tempe and Liquid Waste of Tofu by Using Different Inoculum to Produce Biogas”. The objective of the research was to use liquid waste of tempe and tofu by using different inoculum in producing biogas, finding out the interaction between the waste and microba inoculum in producing biogas, finding out the biggest amount of gas produced by liquid waste of tempe and tofu by using different inoculum in producing biogas and finding out the best time for fermentation in producing biogas. This research was designed by using Factorial Pattern of Complete Random Design (RAL) 2x2 comprising 4 treatments and 3 times repetition. The treatment examined was P1 )Liquid Waste of tempe + Rumen), P2 (Liquid Waste of tofu + Rumen), P3 (Liquid Waste of tempe + Rumen Contents), P4 (Liquid Waste of tofu + cow feces ) with the comparison of every treatment 50% :50%. Based on the research result, it shows that every treatment examined can produce biogas. The highest volume of examined treatment is P1 treatment (Liquid Waste of tempe + Rumen Contents) which was 57.15cm3. The best time for fermentation was the third day (72 hours). Keywords: Liquid Waste of tempe, Liquid Waste of tofu, Inoculum and Biogas.